(untitled) (International Journal of Engineering and Computer Science, 2018)
The objective of this paper is to build a safety system which is integrated with the smart helmet and intelligent bike to reduce the probability of two-wheeler accidents and drunk and drive cases. The pressure sensor and the accelerometer sensor checks if the person is wearing the helmet or not. Alcohol sensors detects the alcoholic content in the rider’s breath. If the rider is not wearing the helmet or there is alcohol content found in rider’s breath, the bike remains off. The bike will not start until the rider wears the helmet and there is no alcoholic content present stating that rider did not consume alcohol. When the rider crashes, helmet hits the ground and sensors detect the motion and tilts of helmet and reports the occurrence of an accident and sends information of the location of accident to the family members of the rider and the emergency contact numbers.